2005
DOI: 10.1073/pnas.0503712102
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting farnesylation reverses the nuclear morphology defect in a HeLa cell model for Hutchinson-Gilford progeria syndrome

Abstract: Hutchinson-Gilford progeria syndrome (HGPS) is a devastating premature aging disease resulting from a mutation in the LMNA gene, which encodes nuclear lamins A and C. Lamin A is synthesized as a precursor (prelamin A) with a C-terminal CaaX motif that undergoes farnesylation, endoproteolytic cleavage, and carboxylmethylation. Prelamin A is subsequently internally cleaved by the zinc metalloprotease Ste24 (Zmpste24) protease, which removes the 15 C-terminal amino acids, including the CaaX modifications, to yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
154
1
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 186 publications
(170 citation statements)
references
References 35 publications
12
154
1
3
Order By: Relevance
“…Thus, processing mutants, but not R527H, act in a dominant fashion to interfere with pRB function. Our data correspond with recent findings suggesting that unprocessed lamin A acts dominantly in laminopathy-based premature aging and that MAD is an autosomal-recessive disorder (37,40,48).…”
Section: Vol 26 2006supporting
confidence: 80%
“…Thus, processing mutants, but not R527H, act in a dominant fashion to interfere with pRB function. Our data correspond with recent findings suggesting that unprocessed lamin A acts dominantly in laminopathy-based premature aging and that MAD is an autosomal-recessive disorder (37,40,48).…”
Section: Vol 26 2006supporting
confidence: 80%
“…In all of these cells, the FTI treatment significantly reduced nuclear shape abnormalities. Other laboratories [82][83][84] also reported that FTIs improved nuclear shape in human HGPS fibroblasts and/or cells that had been transfected with a progerin cDNA.…”
Section: Fti Treatment Inhibits Lamin a Biogenesis In Cultured Cells-mentioning
confidence: 96%
“…On induction (on), a nucleoplasmic and rim localization typical for lamin A is observed. When induced in the presence of farnesyltransferase inhibition (FTI), GFP-prelamin A accumulates within the nucleus in bright foci, as has also been documented by us and others (Capell et al, 2005;Glynn and Glover, 2005;Mallampalli et al, 2005;Toth et al, 2005;Yang et al, 2006). Bar, 50 m. (B) Cycloheximide-chase analysis of preaccumulated nuclear prelamin A upon release from FTI block.…”
Section: The C-terminus Of Zmpste24 Which Contains a Dilysinelike Momentioning
confidence: 99%
“…Such large intranuclear foci have previously been observed under conditions of FTI treatment in several cell types, yet the nature and potential function of these prelamin A-containing foci remains unknown (Capell et al, 2005;Glynn and Glover, 2005;Mallampalli et al, 2005;Toth et al, 2005;Yang et al, 2005). Our data suggest that these foci represent an intermediate in biogenesis rather than dead-end aggregates, because lamin A chases from the foci to the nuclear rim over time in the absence of new protein synthesis ( Figure 2B), but fails to chase to the rim when CaaX processing is blocked ( Figure 2C).…”
Section: Gfp-prelamin a Can Be Processed Within The Nucleusmentioning
confidence: 99%